Az engesztelő mozgalom húsz éve a Székelyföldön - Fábián Gabriella; Szegedi Vallási Néprajzi Konferencia (10.) (2010) (Szeged) (2012)
The expiatory movement began to spread over twenty years ago in the Székelyföld region. The Roman Catholic Gyulafehérvár Archdiocese had parishes in 144 localities in the region. According to the census of 1998 expiation was performed at that time in 40% of them, in 58 parishes. There was little change in this proportion by 2010 when the figure was 38%. Some expiatory communities had ceased to exist, but new ones had arisen. At first the practice of prayers of expiation was confined to private homes, but nowadays it has been introduced into many churches as well. Organisation is no longer exclusively from below. We now find occasions of expiation created at church initiative and under church guidance. The centre of expiation in Csiktaploca has lost the significance it had a decade ago. From the regional viewpoint, it can be said that the expiatory movement is spreading widely in some archdeaconries. There are also examples of expiatory communities comprised of young people.
Keywords: Társadalomtudományok; Szociológia; Bölcsészettudományok; Filozófia, etika és vallástudományok